Transgressive City-Making and Governance Housing Struggles, Occupations and Evictions in the Lisbon Metropolitan Area - Saaristo, S.-M. (2025)
Transgressive City-Making and Governance delves into the pressing global issue of housing exclusion and forced evictions, using Lisbon as a case study. This book, based on a 15-month engaged ethnography, critically examines council housing occupations and evictions, revealing how these practices challenge neoliberal urban governance and put forward alternative forms of urban citizenship. Exploring gendered, classed, and racialised dynamics, it sheds light on the transformative potential of housing occupations and the role of social movements in contesting systemic exclusion. It is essential reading for those interested in housing rights, social justice, and urban governance.